ASSESSMENT OF EFFICACY AND SAFETY OF INACTIVATED RABIES VACCINES BASED ON “ARRIAH” STRAIN AND FORMULATED WITH DIFFERENT ADJUVANTS IN CATTLE - A. N. Balashov; D. A. Lozovoy; A. V. Borisov; D. V. Mikhalishin; M. I. Doronin (Ветеринария сегодня)
Rabies cases are still reported in various mammal species in the Russian Federation. Wild carnivores contacting with domestic and farm animals and transmitting the pathogen to them are the main source and natural reservoirs of rabies. The highest level of rabies incidence in livestock is observed among cattle. Thus, 158 new outbreaks were reported in the Russian Federation in 2017 where the virus was identifi ed in cattle. Rabies specifi c prophylaxis as well as assessment of its effi cacy based on the level of accumulated antirabies virus neutralizing antibodies currently occupy one of the leading positions in the modern system of veterinary and sanitary measures against rabies. The paper presents the study results confi rming effi cacy and safety of three inactivated rabies vaccines based on the “ARRIAH” strain and intended for rabies prevention in cattle. The adsorbed and two emulsion rabies vaccines, formulated with diff erent adjuvants demonstrated innocuity and safety, and induced post-vaccination immunity in all immunized animals at day 21 post inoculation. The mean titers of anti-rabies antibodies were as follows: for inactivated adsorbed vaccine – 4.02 ± 0.76 IU/cm3; for inactivated emulsion vaccines – 16.30 ± 2.03 and 20.73 ± 3.39 IU/cm3. As compared with the adsorbed vaccine, the emulsion vaccines formulated with Montanide ISA 206 and ISA 70 adjuvants induce stronger immunity.